PRINCIPLES OF DEVELOPMENT OF OSMOTICALLY AND BIOLOGICALLY ACTIVE COMPOSITIONS FOR TECHNOLOGIES OF FERMENTED MILK DRINKS - Assembayeva Elmira Kuandykovna,; Galstyan Aram Genrikhovich,; Nurmukhanbetova Dinara Erikovna,; Bazilbayev Saken Muhataevich,; Strizhko Maria Nikolaevna,; Seidakhmetova Zaure Zhunusovna, (Academic Journal of Physical and Chemical Sciences, 2019)
Currently, yogurt is considered to be the most popular dairy product in the world. The high content of skim milk, Bulgarian sticks and thermophilic Streptococcus, the content of which in the finished product at the end of the term is not less than 107 CFU in 1g of the product, create a unique recognizable profile of the product. Taking into account the specifics of Kazakhstan, in particular, geographical, socio-cultural factors, as well as the centuriesold history of camel milk consumption, the problem of scientific justification and development of industrial technologies of yogurt on its basis is actualized. The research presents the results of the development of osmotically active sweetening composition with pronounced probiotic properties. With its use, the technology of the creation of yogurt from camel milk, including low-lactose one, has been developed. It was found that the optimum level of syrup is about 5% by weight of the product. The analysis of the produced yogurt and low-lactose yogurt showed their high organoleptic characteristics. The developed technology suggests the possibility of its implementation in the dairy industry, producing dairy products.